Mapeamento de locos de resistência ao crestamento bacteriano comum do feijoeiro (Phaseolus vulgaris L.) - Passos, Ana Laura Pereira (2016)
The common bean (Phaseolus vulgaris) is grown in Brazil in various locations, soil and climatic conditions. The diseases are among the leading causes of losses in productivity of this legume, and the common bacterial blight (CBB) is the most important bacterioses that affects the culture. The resistance of CBB in common bean is a complex quantitative trait that results from the interaction of several genes. Genetic maps are tools that optimize the search for loci associated with this type of feature, and the most commonly used molecular markers available for this type of study are the SNPs (Single Nucleotide Polymorphism). In this sense, this study aimed to: (i) develop a robust genetic map for common bean using SNP markers and the RIL (Recombinant Inbreed Lines) mapping population derived from Ruda × AND 277; (ii) characterize this RIL population and their parents about the reaction to common bacterial blight in field and greenhouse; and (iii) identifying genomic regions (major genes and/or QTL) that control the bacterial blight in this population. We used 393 individuals of the Ruda × AND 277 RIL population, evaluated for reaction to CBB in two field trials in Ponta Grossa - PR, in the rain growing season of 2012 and 2014 and in an inoculation test at the greenhouse, in Santo Antônio de Goiás - GO. The population was genotyped with 5,398 SNP markers and mapping was performed using the R-OneMap and MapDisto programs. Statistical analyzes were performed in the Genes program, and the Scott-Knott method was used for averages groupingin R platform. The QTL analysis was conducted in QTLCartographer program. Using the chi-square test (1:1), 2,062 markers were selected for mapping. Three genetic maps with high strengt, saturation and resolution were built. Statistical analysis showed that there is genetic variability for the CBB resistance in the population of RILs. The QTL analysis identified 10 QTLs linked to resistance of CBB in the Ruda × AND 277 RIL mapping population, in the chromosomes PV01, PV02, Pv07, Pv09 and PV11, based on results from evaluations carried out in the field and greenhouse. The maps constructed for this population have high strength and resolution and may be used for future work on integrative mapping. The statistical analysis evidenced the quantitative character of resistance to CBB in common bean and showed that the parent Rudá has the CBB resistance alleles. It is expected that the markers linked to these QTLs identified can be used in future studies of marker assisted selection.